Verses of Divine Attributes and Mutashabihat in the Holy Quran and Their Correct Interpretation - Muhammad Usama; Professor Dr. Altaf Hussain Langrial (Journal of Religion and Society, 2025)
The Holy Quran is the sacred and unaltered Word of Allah, offering guidance, direction, and a comprehensive explanation of the perfect religion for all humanity. It clearly and wisely presents various aspects of Allah’s essence, attributes, and actions. However, the Quran also contains certain verses known as Mutashabihat, meaning those verses whose apparent meanings transcend human intellect or the usual linguistic understanding, leading scholars from different schools of thought to offer diverse interpretations.The Divine Attributes refer to those essential qualities inherently belonging to Allah’s Being, such as knowledge, power, life, will, and so forth. The Quran explicitly mentions these attributes in various verses. Yet, there are also verses that describe Allah’s attributes using human terms, such as Allah’s "Hand," "Eye," "Face," and similar expressions. The interpretation of these verses is complex because if these attributes are taken literally as human attributes, it challenges the principle of Tawhid (Divine Oneness). On the other hand, if they are understood entirely metaphorically, the clarity and sanctity of the Quran might be compromised.Different Islamic theological schools, including the Mu'tazilah, Maturidiyyah, and Ash'arites, have presented distinct views on the interpretation of Divine Attributes to preserve the purity of monotheism while honoring the Quranic text. For example, the Mu'tazilah consider Divine Attributes as created to avoid any anthropomorphism, whereas the Maturidiyyah and Ash'arites regard these attributes as essential and uncreated but emphasize allegorical or metaphorical interpretations. To understand the Mutashabihat verses properly, scholars have developed principles of Tafsir (exegesis) and Ta’wil (interpretation) to extract the correct meaning within the limits of reason and scripture. These principles stress that the Divine Attributes should neither be taken in a physical sense nor should their meanings contradict reason. Instead, a balanced and moderate interpretation consistent with the spirit of the Quran and Sunnah is required.This issue is not only central to theological and doctrinal discussions but also holds profound significance in Islamic philosophy, Sufism, and jurisprudence. A proper understanding of the Quranic Attributes and the Mutashabihat verses is indispensable for a correct comprehension of Islam’s fundamental beliefs, particularly Tawhid and Divine Attributes. Therefore, scholarly research, comparison, and authentic interpretation of this subject are essential for preserving doctrinal correctness and intellectual guidance for Muslims. Keywords: Attributes, Mutashabihat, Interpretation, Comprehensive, Indispensable, Interpretation